ETHNO-VETERINARY PRACTICES AMONGST LIVESTOCK FARMERS IN NGAMILAND DISTRICT, BOTSWANA - Gabalebatse, Moabiemang; Ngwenya, Barbara N.; Teketay, Demel; Kolawole, Oluwatoyin Dare (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
We carried out a study to determine ethno-veterinary knowledge used to treat and prevent livestock diseases in Toteng Village in Ngamiland District, northwestern Botswana. Primary data were collected through simple random sampling of 45 households in Toteng. Respondents were either livestock owners or cattle herders. Respondents were interviewed using a structured questionnaire which had both open and closed-ended questions. Cattle ownership or herdership in Toteng is an inter-generational occupation with people ranging from 15 to 94 years old. Cattle were acquired either through inheritance, buying, mafisa (reciprocal exchange) system or government scheme. Women in the study area were more involved in livestock farming activities. Eleven livestock diseases were reported to be prevalent in the study area. The top six diseases were tlhako le molomo -foot and mouth disease (FMD), matlho - eye infections, letshololo-diarrhea, madi -pasteurollosis, mokokomalo - aphosphorisis and pholoso- contagious abortion. At least nine medicinal plant species having ethno-veterinary applications were recorded in the study area. Single plants are mostly used rather than a combination of plants. A number of social strategies were mentioned such as ‘go fetola mafudiso’ - to change grazing areas, and ‘go thaa lesaka’ – to ritualistically ‘protect a kraal’ or livestock against evil spells and predators (lions). Although the intervention of conventional veterinary medicine is pervasive in Toteng, and many livestock owners are resorting to it, there is evidence, however, of generalized ethno-veterinary knowledge used to treat and prevent livestock diseases. Local farmers and their herders in Ngamiland are not only knowledgeable and experienced in treating a range of livestock diseases, but also in performing other veterinary tasks such as assisting in births, treating fractures and range management strategies to mitigate particular threats from their local environment. The efficacy of ethno-veterinary knowledge for preventing and treating livestock diseases and range management strategies identified in this study need to be fully investigated and integrated in veterinary extension services.